Child Marriage Dispensation in Islamic Law: A Meta-Analysis and Systematic Review - Sayehu (PT. Ratu Bilqis Azzahira bekerjasama dengan Fakultas Syariah Universitas Islam Zainul Hasan Probolinggo, 2025)
Child marriage continues to pose a legal and ethical dilemma in many Muslim-majority societies, including Indonesia, where legal reforms have raised the minimum marriage age but left room for exceptions through court dispensations. This study aims to critically examine the practice of child marriage dispensation in the context of Islamic law by conducting a systematic review and meta-analysis using the PRISMA 2020 framework. Eighteen peer-reviewed studies published between 2020 and 2024 were analyzed from scholarly databases including Scopus, PubMed, ScienceDirect, and Mendeley. The findings reveal that the majority of dispensations are granted due to premarital pregnancy and social pressure, often with limited consideration of the child's psychological readiness or long-term welfare. Although religious courts cite Islamic law to justify these decisions, a deeper examination suggests that many rulings prioritize cultural norms over Islamic legal ethics. Through the lens of maqāṣid al-sharī‘ah, the study finds that such practices often conflict with the higher objectives of Islamic law, particularly the protection of life, dignity, and justice. The review concludes that judicial practices surrounding child marriage dispensations require urgent reform through a combination of legal restrictions, religious reinterpretation, and community education to better safeguard children's rights.